Anemia With Febrile Seizure In Children Aged From Six Months Old To Five Years Old At Gotong Royong Hospital Surabaya - Calvindoroputro, Calvindoroputro; Susan, Susan; Meryana, Pauline (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Febrile seizure is one type of seizure that commonly occurs in groups of children less than five years of age, especially at the age of 2 years. The incidence of febrile seizures in children is often very worrying for parents. Aim: The purpose of the study was to examine the relationship of anemia with the occurrence of febrile seizures in children aged six months - five years old at Gotong Royong Hospital Surabaya. Methods: This study uses an Observational Study carried out with a case-control design and purposive sampling method. The study was conducted in one bone that took place between July 25 and August 25, 2017. The study was conducted by taking secondary data from medical records of children aged six months - five years who were hospitalized, consisting of 21 children with febrile seizure and 21 children with fever without a seizure, and Hb recorded in hospitalized patients. Analyze with the chi-square test. Results: Children with anemia, 8.5 times more likely to experience febrile seizures than children who did not experience anemia. Conclusion: The results showed a significant relationship between anemia and febrile seizure (p = 0.002) with an odds ratio of 8.5. Therefore, children with anemia have a higher risk of having a febrile seizure.